Variabilidad climática y oceanográfica en el Atlántico Norte subpolar durante el Pleistoceno (1.050.000-403.000 años) - Martínez Sánchez, Marta (2017)
[EN] This Thesis is a high resolution micropaleontological study of the IODP Site U1314, recovered during the IODP 306 Expedition, in the Gardar Drift formation (southern Iceland), in the subpolar North Atlantic. The main purpose of this Thesis is the study of climatic variations at different time scales (orbital and suborbital) and the evolution of surface circulation patterns in the North Atlantic through changes in the associations of cocolitophorids that occurred during the interval between 1,050,000 and 400,000 years (MIS 30-11); known as the Middle Pleistocene Transition. The reason for studying the coccolitophorids assemblages’ variations is due to the fact that they conform one of the main components of the phytoplankton in the current oceans. These organisms secrete calcified plaques (cocoliths) that, after sedimentation in the seabed, can be preserved in the fossil record. Coccolithophore abundance and diversity are highly influenced by the environmental conditions that prevailed at time these organisms inhabited the ocean. Hence, the study of coccoliths preserved in the sedimentary record provides useful information to perform paleoenvironmental reconstructions. In this Doctoral Thesis, a record of calcareous nanofossils has been analyzed in the interval from MIS 11 to 30. In addition, statistical and mathematical analyses of the calcareous nanofossils assemblage, especially the spectral analysis and the analysis of delays between different variables (LAG), have been made in order to know the responsetime between two systems (or sites) affected by the same climatic effect. We have also compare our study with site MD03-2699 (southern of site U1314), with the aim of reconstructing how and when the NAC (North Atlantic Current) could vary in the MIS 11-14 interval. The importance of this study, located in the North Atlantic and specifically the subpolar North Atlantic, is related to the sensitivity of the area to climatic and oceanographic changes. The surface oceanographic regime is strongly imprinted by the Subpolar gyre, specifically by the NAC, which feeds the IC (Irminger Current). When the NAC and the IC arrive at high latitudes, they will sink generating deep waters masses. Oceanographic changes at deep waters are important in this area because it is a deepwater formation zone (Labrador Sea and Norwegian Sea-Greenland), which is the motor of the thermohaline circulation and affect the global circulation. The calcareous nanofossils asemblages showed abrupt changes between the warm interval assemblage, where the total abundance of species is greater and dominated by the species associated to the IC and the cold interval assemblage where the total abundance is low and the species associated with waters of the IC abruptly decline. These abrupt changes are due to the latitudinal variation of the NAC waters and the cold waters from farther north, which ultimately determine the position and variation of the IC waters. This variation of the waters throughout the study interval allows us to reconstruct four scenarios of surface water circulation: High advection of the Irminger waters, low advection of the Irminger water, advection of polar water and terminations. The analysis of the cyclicity of the different records elaborated in this Thesis has shown that the associations of nanofossils have been affected by the three orbital parameters: eccentricity, obliquity and precession, which have allowed to observe a progressive increase in the importance of the precession in the climate cycles, which could affect the insolation on the sea surface, which ultimately affected the position of the ocean currents. [ES] El estudio de los eventos climáticos abruptos y de los mecanismos implicados representan uno de los mayores retos a los que se enfrenta la investigación climática hoy en día. La identificación de los mecanismos de retroalimentación entre los sistemas océano- atmósfera-criosfera son de vital importancia para la comprensión de la variabilidad climática presente en registros sedimentarios del fondo oceánico. Entender cómo y por qué ocurrieron los cambios climáticos del pasado nos puede ayudar a predecir futuros escenarios relacionados con cambios climáticos. En esta Tesis se aportan nuevos datos y enfoques sobre los cambios climáticos y oceanográficos que se registraron entre aproximadamente 1,050,000 y 400,000 mil años en las latitudes altas del Atlántico Norte y que se relacionan con el clima y la circulación oceánica global. El Atlántico Norte subpolar está considerado como una de las regiones climáticas más sensibles de la Tierra y es la llave fundamental para la compresión de la de la circulación de retorno (AMOC) en el Atlántico. Las variaciones de los parámetros superficiales influyen en la circulación y en la formación de masas de agua profundas, explicando por qué las variaciones entre periodos glaciares e interglaciares afectan a la formación de agua profunda, a cómo el calor se distribuye en el océano y a la distribución vertical de nutrientes que afectan a las comunidades planctónicas. El intervalo de tiempo estudiado en esta Tesis Doctoral está caracterizado por la asimetría en los ciclos climáticos y contiene la llamada “transición del Pleistoceno medio”, entre los 1.1 y 0.6 Ma, caracterizados por una reorganización climática que se ha registrado en sedimentos marinos y continentales y se caracteriza por cambios a nivel global, entre los cuáles se incluyen cambios en temperatura del mar, nivel del mar y masas de hielo y afectó a la distribución y evolución de la vida en la Tierra, incluyendo a los ancestros de los seres humanos modernos. Durante la primera parte del intervalo de estudio, predominan los ciclos de ~100 ky que habían surgido entre los 950-900 ka mostrando un aumento progresivo en la intensidad de los periodos glaciales, produciéndose grandes acumulaciones de hielo en el hemisferio norte. Sin embargo, no es hasta aproximadamente los 400 ka (durante el periodo llamando “Evento Mid-Brunhes”) cuando los ciclos de ~100 ka adquieren su mayor amplitud, caracterizándose por periodos glaciales muy fríos e interglaciales muy cálidos. Dada la estrecha relación entre hidrosfera y criosfera, esta reconfiguración del volumen de hielo global tuvo gran repercusión en los patrones de circulación oceánica superficial y profunda a nivel global y muy especialmente en la región del Atlántico Norte. Establecer cuáles son los mecanismos de retroalimentación implicados en esta reconfiguración del sistema climático a escala orbital y suborbital representa uno de los grandes retos de la paleoclimatología moderna que se trataran en esta Tesis. El trabajo presentado se basa en el análisis de una secuencia sedimentaria del sondeo marino profundo U1314, perforado en la formación Gardar Drift (sur de Islandia), durante la Expedición 306 del Integrated Ocean Drilling Program (IODP) en el Atlántico Norte subpolar. El material recuperado proporciona un registro de alta resolución del intervalo comprendido entre 1.050.000 y 400.000 años.